Age and gender effects on the prevalence of poor sleep quality in the adult population - Juan J. Madrid-Valero; José M. Martínez-Selva; Bruno Ribeiro do Couto; Juan F. Sánchez-Romera; Juan R. Ordoñana (Elsevier, 2017)
Objective: Sleep quality has a significant impact on health and quality of life and is affected, among other factors, by age and sex. However, the prevalence of problems in this area in the general population is not well known. Therefore, our objective was to study the prevalence and main characteristics of sleep quality in an adult population sample. Methods: 2,144 subjects aged between 43 and 71 years belonging to the Murcia (Spain) Twin Registry. Sleep quality was measured by self-report through the Pittsburgh Sleep Quality Index (PSQI). Logistic regression models were used to analyse the results. Results: The prevalence of poor sleep quality stands at 38.2%. Univariate logistic regression analyses showed that women were almost twice as likely as men (OR: 1.88; 95% confidence interval [95%CI]: 1.54 to 2.28) to have poor quality of sleep. Age was directly and significantly associated with a low quality of sleep (OR: 1.05; 95%CI: 1.03 to 1.06). Conclusions: The prevalence of poor sleep quality is high among adults, especially women. There is a direct relationship between age and deterioration in the quality of sleep. This relationship also appears to be more consistent in women.